The Rome Pavilion at the Italian General Exhibition in Turin in 1884: the exposition of Maps and Plans of Rome by Giovanni Battista de Rossi and the City Museum (ACME, 2023)
The paper contributes to the reflection on how the 19th-century national events of wider appeal such as the Art and Industrial Exhibitions fostered the dissemination and enhancement of archaeological discoveries. The specific case of the ‘Exhibition of the City of Rome’, held during the Turin Exhibition in 1884, is examined as a paradigmatic example of the archaeologist Giovanni Battista de Rossi’s commitment to promoting Rome in united Italy, using archive and press documents of the time. The Roman pavilion at Turin in 1884, for which de Rossi was responsible for the medieval section, is presented as a key event in the dissemination of Roman archaeological discoveries after 1870 and as a major event in the promotion of studies of Roman topography strongly desired by de Rossi, and which can be read as the starting point for the setting up of the Museum of the City of Rome.